2022
DOI: 10.1556/063.2022.00113
|View full text |Cite
|
Sign up to set email alerts
|

Moving beyond ideological problem-solving paradigms in higher education governance studies: Toward a renewed perspective

Abstract: New Public Management (NPM)-inspired higher education (HE) governance has become increasingly topical in recent years. However, while existing research provides an overall understanding of relevant changes, it does not offer a complete analysis of complex governance and falls prey to deterministic and relatively narrow ideological impositions. Scholars are overwhelmingly oriented toward governance models or modes and the ideas of efficiency, effectiveness, and competition in NPM. They either promote these aspe… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
0
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
2

Relationship

0
2

Authors

Journals

citations
Cited by 2 publications
(1 citation statement)
references
References 49 publications
0
0
0
Order By: Relevance
“…In terms of infrastructure, policies should be developed to ensure teachers' accessibility to necessary technology, hardware, and software for providing virtual instructional. Several research endeavours reported the need for revising polices related to technical resources provisions in higher education (Afrianty et al, 2022;Ashour et al, 2021;Molla & Cuthbert, 2023;Nguyen et al, 2023;Yembergenova, 2023). These resources not only include new gadgets and hardware, but also subscriptions to different audio/video development software and content creation software.…”
Section: Discussionmentioning
confidence: 99%
“…In terms of infrastructure, policies should be developed to ensure teachers' accessibility to necessary technology, hardware, and software for providing virtual instructional. Several research endeavours reported the need for revising polices related to technical resources provisions in higher education (Afrianty et al, 2022;Ashour et al, 2021;Molla & Cuthbert, 2023;Nguyen et al, 2023;Yembergenova, 2023). These resources not only include new gadgets and hardware, but also subscriptions to different audio/video development software and content creation software.…”
Section: Discussionmentioning
confidence: 99%